2015
DOI: 10.1002/anie.201508639
|View full text |Cite
|
Sign up to set email alerts
|

Click Functionalization of a Dibenzocyclooctyne‐Containing Conjugated Polyimine

Abstract: A conjugated poly(phenyl-co-dibenzocyclooctyne) Schiff-base polymer, prepared through polycondensation of dibenzocyclooctyne bisamine (DIBO-(NH2)2) with bis(hexadecyloxy)phenyldialdehyde, is reported. The resulting polymer, which has a high molecular weight (M(n)>30 kDa, M(w)>60 kDa), undergoes efficient strain-promoted alkyne-azide cycloaddition reactions with a series of azides. This enables quantitative modification of each repeat unit within the polymer backbone and the rapid synthesis of a conjugated poly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
39
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 66 publications
2
39
0
Order By: Relevance
“…Consistent with our previous work, we found that the apparent molecular weight of the product polymer decreased upon SPAAC coupling, changing from 26.1 kDa (M n ) to a range between 17.8 and 22.0 kDa ( Table 1). The observed decrease in molecular weight is consistent with our previous studies, 23 where computational modeling, including density functional theory (DFT) and semi-empirical calculations, showed a conformational change in the polymer backbone that resulted in its "accordion-like" contraction upon click functionalization. 23 This contraction is manifested in an apparent decrease in hydrodynamic volume for most of the polymers.…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…Consistent with our previous work, we found that the apparent molecular weight of the product polymer decreased upon SPAAC coupling, changing from 26.1 kDa (M n ) to a range between 17.8 and 22.0 kDa ( Table 1). The observed decrease in molecular weight is consistent with our previous studies, 23 where computational modeling, including density functional theory (DFT) and semi-empirical calculations, showed a conformational change in the polymer backbone that resulted in its "accordion-like" contraction upon click functionalization. 23 This contraction is manifested in an apparent decrease in hydrodynamic volume for most of the polymers.…”
Section: Resultssupporting
confidence: 91%
“…The strained alkyne‐containing polymer, P0 , was synthesized following previously reported procedures . Azides for P1 , P2 , and P7 (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The resulting poly(HFIPA‐ alt ‐OVE) was orthogonally postfunctionalized via radical thiol–ene click reaction and subsequent amidation . It is well known that the properties of polymers can be altered significantly by chemical postfunctionalization and numerous recent reports deal with the modification of polymers by thiol click chemistry, Cu‐catalyzed alkyne–azide click reaction (CuAAC), amidation reactions, and many others, including combinations thereof. Our conceptual approach introduced allowed for preparation of a small library of alternating copolymers using a single type of parent copolymer and diversifying subsequent orthogonal postmodification.…”
Section: Methodsmentioning
confidence: 99%